Analisis Potensi Pariwisata di Desa Wisata Sedau: Identifikasi Atraksi, Aksesibilitas, Amenitas, Akomodasi, dan Aktivitas Wisata - Herman Herman; Putri Rizkiyah; Achlan Fahlevi Royanow; Saiful Fahmi; Hendri Yadi Saputra (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
The Sedau Tourism Village in West Lombok has great tourism potential, however, it is still focused on the natural attractions of Gunung Jae as the main attraction. This study aims to analyze the potential of tourism products in this village using the 5A approach, which includes attractions, accessibility, amenity, accommodation, and tourism activities. This study used a qualitative approach through a field study, with data collection through observation and interviews with 8 informants including the management of the Pokdarwis, homestay owners, UMKM actors, art actors, and operators of tourist attractions. The results found that Sedau Tourism Village offers a variety of natural, cultural and man-made attractions, but accessibility and supporting facilities are still a challenge, while accommodation limited to homestays needs to be developed. Diversification of tourism activities is also urgently needed to increase the attractiveness of this village. This research recommends improving road infrastructure, providing eco-friendly transportation, and developing supporting facilities and community-based accommodation. In addition, the utilization of digital technology, such as virtual tour applications, is also suggested to improve the introduction and experience of tourism in Sedau Tourism Village.